Moving image installation, the embodied spectator of cinema and Amar Kanwar: Learning from intermediality. (1st September 2014) - Rutherford, Anne
This article juxtaposes cinema and moving image installation to question the ways cinema studies has understood embodied spectatorship. Through a close study of Amar Kanwar's moving image installation, The Sovereign Forest, exhibited at 'documenta 13', the article draws on an intermedial approach to explore emerging transformations in the phenomenological dynamics of the moving image. The article explores how the concrete, multisensory experience of Kanwar's installation trains the sensorium of the viewer, opening new possibilities for the moving image. This concrete physicality serves as a point of reference to refocus and sharpen the understanding of the more complex kinaesthetic dimensions of cinema spectatorship.